Size, weight, and expectations. (May 2022) - Smeets, Jeroen B.J.; Vos, Kim; Abbink, Emma; Plaisier, Myrthe
The size-weight illusion is well-known: if two equally heavy objects differ in size, the large one feels lighter than the small one. Most explanations for this illusion assume that because the information about the relevant attribute (weight itself) is unreliable, information about an irrelevant but correlated attribute (size) is used as well. If such reasoning is correct, one would expect that the illusion can be inverted: if size information is unreliable, weight information will be used to judge size. We explored whether such a weight-size illusion exists by asking participants to lift Styrofoam balls that were coated with glow in the dark paint. The balls (2 sizes, 3 weights) were lifted using a pulley system in complete darkness at 2 distances. Participants reported the size using free magnitude estimation. The visual size information was indeed unreliable: balls that were presented at a 20% larger distance were judged 15% smaller. Nevertheless, the judgments of size were not systematically affected by the 20% weight change (differences < 0.5%). We conclude that because the weight-size illusion does not exist, the mechanism behind the size-weight illusion is specific for judging heaviness.